Bilateral Sudden Sensorineural Hearing Loss: A Distinct Phenotype Entity. Issue 4 (2nd April 2022) - Elias, Thaís Gomes Abrahão; Monsanto, Rafael da Costa; Jean, Line-Dore Saint; de Souza, Lucas Sonzzini Ribeiro; Penido, Norma de Oliveira
Abstract : Objective: To investigate the clinical phenotype and hearing prognosis of patients with unilateral and bilateral (simultaneous and nonsimultaneous) sudden sensorineural hearing loss (SSNHL). Study Design: Retrospective cohort. Setting: Otology outpatient clinic of a tertiary university hospital. Patients: Three hundred eighty-five medical records from patients with SSNHL. Main Outcome Measure(s): Comparison of demographic, clinical, and audiometric (pretreatment and posttreatment) data of patients with unilateral and bilateral SSNHL. Results: Our final analysis comprised of 239 medical records of patients with SSNHL. Most patients had unilateral SSNHL (186, 77.82%). We identified a potential underlying cause for the SSNHL in 105 (43.9%) of the cases, being more frequent in cases of bilateral simultaneous SSNHL (100%) as compared with unilateral (45.6%) and nonsimultaneous bilateral SSNHL (22.7%). Cases of simultaneous bilateral SSNHL presented more frequently with severe or profound hearing loss (89%; unilateral SSNHL 50.5%; nonsimultaneous bilateral SSNL, 59.1%) and had a significantly worse hearing recovery prognosis as compared with unilateral or nonsimultaneous bilateral SSNHL ( p  = 0.002). Conclusion: We observed a high heterogeneity of clinical presentations of SSNHL, the most common being unilateral SSNHL. Our results demonstrate that the clinical and audiological prognosis of simultaneous bilateral SSNHL differed significantly from unilateral and nonsimultaneous bilateral SSNHL, suggesting that simultaneous cases of bilateral SSNHL may be a part of a different disease process. The presence of a simultaneous, bilateral SSNHL indicates the need to investigate the presence of an underlying systemic disease.